Hubungan Status Pekerjaan Ibu dengan Keberhasilan ASI Eksklusif - Eni Subiastutik (Akademi Kebidanan Aifa Husada Madura, 2023)
The low level of exclusive breastfeeding is a health issue in the world. Breast milk has nutritional needs that are suitable for babies aged 0-6 months. According to WHO (2021), the prevalence of exclusive breastfeeding in the world is still around 44%. Several factors can lead to low coverage of exclusive breastfeeding, one of which is the mother's employment status. According to BPS data (2022), the prevalence of working women is around 36.20%. The purpose of this study was to analyze the relationship between the mother's employment status and exclusive breastfeeding. This research is a literature review research with a systematic mapping study design. Data sources come from previous research published within the last five years, searches through the Google Scholar database and the Garuda Portal. Researchers screened through flowcharts according to PEOS criteria and obtained 7 national articles and 3 international articles, research subjects were mothers who had babies aged more than 6 months. The results of all articles show that the majority of mothers with status are not working (22.5% -87.1%) and the majority of babies are not given exclusive breastfeeding (12.9% -79.16%). As much as (5.2% -60%) working mothers do not give exclusive breastfeeding to their babies. Of the 10 articles, there were 9 articles showing the results that there was a relationship between the mother's employment status and exclusive breastfeeding and 1 article shows that there is no relationship between mother's employment status and exclusive breastfeeding. Mothers who work and breastfeed can influence mother's behavior in exclusive breastfeeding. Work is not an obstacle to the failure of exclusive breastfeeding in the first six months of a baby's life, because breastfeeding can be done directly or indirectly. The importance of optimizing mother's understanding and family support in building mothers' confidence to provide exclusive breastfeeding to their babies through the Exclusive Breastfeeding Care Movement, counseling, breastfeeding corner facilities, reducing formula milk advertisements through various media, continues to be increased